Strength Analysis of 230 Feet Coal Barge Deck Using Finite Element Method - Achmad Hanif Prastiawan; Kharis Abdullah (WAVE: Jurnal Ilmiah Teknologi Maritim, 2025)
Coal barges are one of the vital transportation in the coal mining industry to transport large loads by sea or river. The durability of the deck structure is a crucial aspect in ensuring operational safety and efficiency. This study will analyze the strength of a 230-foot coal barge deck using the Finite Element Method (FEM) with different plate thickness variations. The analysis was carried out by modeling the deck structure in Autodesk Autocad software and simulating it in Ansys Workbench software. The purpose of this study was to evaluate the distribution of maximum stress and safety factor at maximum loading conditions. From the analysis results, it was found that the deck cargo model A with a plate thickness of 10 mm had a maximum stress of 175.65 Mpa and a safety factor value of 1.22. While the deck cargo model B with a plate thickness according to the Ultrasonic Test results had a maximum stress of 181.71 Mpa and a safety factor value of 1.18. So the results of the maximum stress and safety factor values ​​of the two models still meet the permissible stress of the material and the safety factor value with the BKI standard.